TNF- α expression on rats after Candida albicans inoculation and neem (Azadirachta indica) extract feeding - I Dewa Ayu Ratna Dewanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Neem is a known traditional medicine from trees which function as immunomodulator. Candidiasis found in mouth is 80% caused by Candida albicans (C. albicans). Immunity is important to limit C. albicans since medicine price is relatively traditional medicine may become a good choice. In the other side the medicine price may not be reached by the citizen, cause citizen choose the traditional medicine. Purpose: The research is aimed to explain of TNF-α expression on rats after inoculated by C. albicans and fed with neem extract (Azadirachta Indica). Methods: There were 5 groups, the first group which was called as control group (KO) hadn’t been fed aqueous extract from neem leaves and was not inoculated by C. albicans, the other group (treatment) was classified into 4 groups. The first group was inoculated by C. albicans only (KP1), second group was fed with 50 mg/day/kg body weight aqueous extracts from Neem leaves, then inoculated with C. albicans starting from day 8 until day 21 (KP2), third group was fed with 100 mg/day/kg body weight aqueous extract from Neem leaves, then inoculated with C. albicans start from day 8 until day 21 (KP3), fourth group was fed with 200 mg/day/kg body weight aqueous extract from Neem leaves, then inoculated by C. albicans start from day 8 until day 21 (KP4). The data was collected from by swabbing the rat’s tongue to calculate C. albicans colonies. The rats were acclimated and collected for immunohistochemistry measurement. Results: The study showed that there were different result on ANOVA, HSD test, and linier regression. ANOVA showed significant difference (p < 0.01) between groups. The HSD test showed significant difference (p < 0.05) between each groups. TNF-α was the stimuli sensor from environment, and used as parameter to see the effect from the change of innate immunity component to C. albicans. Conclusion: Aqueous extract from neem leaves increased the macrophage TNF-α expression on in rat in oculated with C. albicans. Latar belakang: Mimba merupakan salah satu tanaman obat tradisional yang telah dikenal masyarakat dan berfungsi sebagai imunomodulator. Penyakit infeksi yang paling banyak dijumpai di rongga mulut (80%) adalah kandidiasis dengan penyebab utama Candida albicans (C. albicans). Di mana peran imunitas sangat penting pada C. albicans. Di sisi lain harga obat yang semakin mahal semakin tidak terjangkau masyarakat, menyebabkan masyarakat memilih obat tradisional. Tujuan: Riset ini untuk menjelaskan tentang ekspresi TNF-α makrofag pada tikus wistar yang diinokulasi C. albicans dan diberi konsumsi ekstrak cair daun mimba. Metode: Penelitian ini terbagi menjadi 5 kelompok, kelompok kontrol (KO) tidak diberi perlakuan, kelompok yang diinokulasi C. albicans (KP1), kelompok yang diberi konsumsi 50 mg/hari/kg dan diinokulasi C. albicans mulai dari hari 8 sampai hari 21 (KP2), kelompok yang diberi konsumsi 100 mg/hari/kg dan diinokulasi C. albicans mulai dari hari 8 sampai hari 21 (KP3), kelompok yang diberi konsumsi 200 mg/hari/kg dan diinokulasi C. albicans mulai dari hari 8 sampai hari 21 (KP4). Data dikumpulkan dari swabbing lidah untuk dihitung koloni C. albicans dan jaringan lidah dengan metode immunohistochemistry untuk penghitungan sel makrofag yang mengekspresikan TNF-α. Hasil: Studi menunjukkan terdapat perbedaan yang signifikan dari hasil ANOVA, uji HSD, regresi linier. ANOVA menunjukkan perbedaan (p < 0,01) antar kelompok. Uji HSD menunjukkan perbedaan (p < 0,05) antar kelompok. Hal ini dapat dikatakan bahwa TNF-α adalah sensor stimuli dari lingkungan, yang digunakan sebagai parameter untuk melihat pengaruh dari > perubahan dari komponen respons innate terhadap C. albicans. Kesimpulan: Ekstrak cair daun mimba dapa meningkatkan ekspresi makrofag TNF-α dari tikus yang diinokulasi C. albicans.